IMPLEMENTASI KURIKULUM 2013 BAGI PESERTA DIDIK BERKEBUTUHAN KHUSUS DI SMK INKLUSIF - Kamaliah, Dina (Jurnal Pendidikan Khusus, 2016)
ABSTRACT The research objective to describe the 2013 curriculum implementation, as well as the challenges and solutions in the2013 curriculum implementation for PDBK at State Vocational High School 2  Malang. This study used a qualitative descriptive approach. The data collection technique used interviews, observation, and documentation. Data were analyzed through the data reduction, a data display, and conclusion drawing / verification. Technique authenticity of data used triangulation. The results showed that 1) the implementation of the 2013 curriculum for special needs learners on the sport subjects, as well as on the productive subjects in department hotel accommodation and network computer there was small modifications curriculum which was adjusted with the objectives, content, process and evaluation. Modifications was done in the indicators of success, media, time, place, the learning process and learning evaluation 2) There were some problems that include constraints of teachers in the process of presenting the material (for example: how to communicate with the lips motion), the next problem about learning process that required the active role of learners while special needs learners who had particular barriers (for example through obstacles in cognitive, psychomotor, and affective), other constraints regarding more detailed assessment process than the previous curriculum that included knowledge, skills, and behaviour aspects. 3) The chosen solution to this dilemma was the provision of additional information to the regular teachers about special needs learners and learning methods that were appropriate for PDBK, that teachers also needed to get advanced training on the 2013 curriculum until the assessment process, the other solution was to assign Special Educators Teacher (GPK) in the creating of subject teachers joint learning program.   Keywords: implementation, curriculum, special needs learners,  inclusive school